The Pricing of Initial Public Offers of Corporate Straight Debt - DATTA, SUDIP; ISKANDAR-DATTA, MAI; PATEL, AJAY (Journal of Finance, 1997)
ABSTRACT This study examines the initial‐day and aftermarket price performance of corporate straight debt IPOs. We find that IPOs of speculative grade debt are underpriced like equity IPOs, while those rated investment grade are overpriced. IPOs of investment grade debt are typically issued by firms listed on the major exchanges and underwritten by prestigious underwriters. In contrast, junk bond IPOs are more likely to be handled by less prestigious underwriters and are typically issued by OTC firms. Our analysis also reveals that bond rating, market listing of the firm, and investment banker quality are significant determinants of bond IPO returns.